Interactions of multiple cracks in a transversely isotropic piezoelectric plane under mixed mode condition. (July 2017) - Monfared, M.M.; Ayatollahi, M.
Highlights: Stress analysis is carried out in piezoelectric materials weakened by multiple cracks. Dislocation densities are employed to determine mixed mode stress intensity factors. Formulation is applicable for multiple cracks. Both Impermeable and permeable crack surface conditions are considered. Abstract: In this paper, the interactions of multiple cracks in a piezoelectric material under the action of in-plane electromechanical loads are considered. The analytical solution of electric and Volterra climb and glide edge dislocations in an infinite piezoelectric plane are initially obtained by using the Fourier transform. The problem is then formulated by the distributed dislocation technique into a system of singular integral equations where the unknown variables are dislocation density functions on the surfaces of the cracks. These equations are solved numerically for dislocation density functions on the cracks which are used to determine field intensity factors. The results are highly affected by the interaction between multiple cracks and various loading conditions.